Controlled growth of Faujasite zeolite with NaX topology by manipulating solution aging and Na2O/Al2O3 ratios - Mohd Nazir, L.S. (Elsevier B.V., 2020)
Controlled growth of Faujasite zeolite with NaX topology by manipulating the synthesis parameters has been successfully demonstrated in this work. The effects of solution aging durations and Na2O/Al2O3 ratios toward the formation of NaX zeolite are investigated. The morphology, Si/Al ratio, crystallinity and purity, particle size distribution of the resultant NaX zeolite crystals were determined by using field emission scanning electron microscope (FESEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction analyser (XRD) and dynamic light scattering (DLS), respectively. The results showed that, longer aging duration and higher Na2O/Al2O3 ratio resulted in smaller particle size of NaX. On the other hand, high purity of NaX zeolite particle with mean particle size of 750 nm was produced at aging duration of 48 h and Na2O/Al2O3 ratio of 19. Overall, this work has proved that, the growth of NaX zeolite particles could be controlled via a simple synthesis method without using an organic structure directing agent. Â© 2020 Elsevier B.V.